2018
DOI: 10.26417/ejss.v1i3.p34-44
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Crimes against Women: Qualification and Means

Abstract: Crimes against women are constantly changing, especially with the emergence of electronic means to express them. Thus, violence against women using electronic means, has become a phenomenon with multifaceted manifestations and causes also multiple, it must be measured in all its aspects to combat it effectively. Of course, violence also takes place in the context of a relationship of power and domination, which explains why electronic violence predominates over female violence, which remains largely contained.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Most alarmingly, 38% of the victims mentioned that reporting to law enforcement authorities has not been at all helpful. Boukemidja (2018, p. 35) has mentioned that even though the Internet is relatively new, one in ten women suffers from cyber violence by the age of 15. Singh reported that The study conducted by Ms Jyoti Rattan reveals that about 60 per cent of all websites are sexual in content.…”
Section: Brief Critical Review Of Literaturementioning
confidence: 99%
“…Most alarmingly, 38% of the victims mentioned that reporting to law enforcement authorities has not been at all helpful. Boukemidja (2018, p. 35) has mentioned that even though the Internet is relatively new, one in ten women suffers from cyber violence by the age of 15. Singh reported that The study conducted by Ms Jyoti Rattan reveals that about 60 per cent of all websites are sexual in content.…”
Section: Brief Critical Review Of Literaturementioning
confidence: 99%